Strategies for Reversing the Effects of Metabolic Disorders Induced as a Consequence of Developmental Programming - Vickers, Mark H.; Sloboda, Deborah M. (Frontiers in Physiology, 2012)
Obesity and the metabolic syndrome have reached epidemic proportions worldwide with far-reaching health care and economic implications. The rapid increase in the prevalence of these disorders suggests that environmental and behavioural influences, rather than genetic causes, are fuelling the epidemic. The developmental origins of health and disease hypothesis has highlighted the link between the periconceptual, fetal and early infant phases of life and the subsequent development of metabolic disorders in later life. In particular, the impact of poor maternal nutrition on susceptibility to later life metabolic disease in offspring is now well documented. Several studies have now shown, at least in experimental animal models, that some components of the metabolic syndrome, induced as a consequence of developmental programming, are potentially reversible by nutritional or targeted therapeutic interventions during windows of developmental plasticity. This review will focus on critical windows of development and possible therapeutic avenues that may reduce metabolic and obesogenic risk following an adverse early life environment.